Pancreatic β Cell Mass Death - Marrif, Husnia I.; Al-Sunousi, Salma I. (Frontiers in Pharmacology, 2016)
Diabetes is a challenging metabolic disorder for which a cure has not yet been found. Its etiology is associated with two phenomena: a significant loss of the insulin-producing beta cell (β cells) mass and a progressively programmed cell death. Current research in diabetes, however, has taken a different direction; one that moves from compensatory attempts to increase insulin secretion to one that seeks to develop a deep understanding of how to enhance cell survival, decrease apoptosis and replenish β cell mass. The goal of this review is to cover the current knowledge of pancreatic cell development, β cell mass formation and death.